Analisis Fatwa DSN-MUI No. 73/DSN-MUI/XI/2008 tentang Musyarakah Mutanaqisah - Najib, M. Thoha Ainun; Ilmiyah, Izzatul (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The Murabahah contract, which has long been widely used by Islamic banking institutions to realize their financing functions, has shown several weaknesses, despite being a relatively certain and simple mode to implement. Such certainty, however, becomes a drawback for banks when the banking industry, including Islamic banks, must adjust the amount of credit payments made by customers in accordance with prevailing interest-based models within Islamic banking systems. The objective of this study is to analyze the legal foundations, rationality, and relevance of implementing the Musyarakah Mutanaqisah contract as a solution to the weaknesses of the Murabahan contract in modern Islamic financing. The research methodology employed in this study is library research, which involves examining various primary and secondary sources such as the fatwas of the National Sharia Council og the Indonesian Ulema Council (DSN-MUI), opinions of classical scholars related to partnership-based financing. The findings of this study indicate that the ijtihad of DSN-MUI in formulating the fatwa on Musyarakah Mutanaqisah is strongly supported by both naqli arguments and the views of previous scholars. Although Musyarakah Mutanaqisah represents a new form of business partnership, the application of a hybrid contract approach can serve as an innovative solution for Islamic banking, providing both convenience and fairness for customers